Timely Estimates of 5-Year Relative Survival for Patients With Cervical Cancer: A Period Analysis Using Cancer Registry Data From Taizhou, Eastern China - Lu, Hongsheng; Li, Lu; Cheng, Yongran; Yang, Zhaohui; Cao, Xuequan; Zhang, Hui; Qiao, Dongju; Wang, Liangyou; Chen, Tianhui (Frontiers in Public Health, 2022)
Objectives: While timely assessment of long-term survival for patients with cervical cancer is essential for evaluation on early detection and screening programs of cervical cancer, those data are extremely scarce in China. We aimed to timely and accurately assess long-term survival for patients with cervical cancer in eastern China, using cancer registry data from Taizhou, eastern China. Methods: Patients diagnosed with cervical cancer during 2004-2018 from four cancer registries with high-quality data from Taizhou, eastern China were included. Period analysis was used to calculate 5-year relative survival (RS) for overall and the stratification by sex, age at diagnosis and region. Additionally, projected 5-year relative survival (RS) of cervical cancer patients during 2019-2023 was evaluated, using model-based period analysis. Results: Overall 5-year RS for patients with cervical cancer during 2014-2018 reached 90.9%. When stratified by age at diagnosis, we found a clear age gradient for 5-year RS, declining from 95.6% for age<45 years to 68.7% for age>74 years, while urban areas had higher 5-year RS compared to rural areas (92.9% vs. 88.6%). We found a clear increasing trend of 5-year RS during 2004-2018 for overall and the stratification by region and age at diagnosis. Projected overall 5-year RS reached 94.2% during upcoming 2019-2023. Conclusions: We found that, for first time in China using period analysis, most up-to-date (during 2014-2018) 5-year RS for patients with cervical cancer reached 90.9%. Our data have important implications for timely evaluation on early detection and screening programs for patients with cervical cancer in eastern China.